ANALISIS PENGARUH PELATIHAN DAN KEDISIPINAN TERHADAP KINERJA KARYAWAN DINAS PENDAPATAN, PENGELOLAAN KEUANGAN DAN ASET DAERAH (DPPKAD) PEMKOT BATU - Dullah, Muhammad (Manajemen & Bisnis Jurnal, 2016)
A vompany is a place where the employees survive their life and to reach their hope to fulfill their own and their families needs. Thus, the company should give best service for its employees. The company built to get profit from the products or service which were it have made. Moreover, for long-term period, the company should attempt to increase and to develop its business position in order to join high business challenging. To reach that objective, the company should develop its product’s or service’s quality which were the company have made by inceasing its employees’ performance. The increasing of employees’ dicipline. Based or the explanation above, attempts to make a title “An Analisis of Effect of Training and Discipline to the Employees’ performance at Dinas Pendapatan, Pengelolaan Keuangan dan Aset Daerah (DPPKAD) Pemkot Batu”. This research is done to detect training variable influence (X1) and Discipline variable (X2) towrds empoyee performance,. This watchfulnee kind eksplanatori with sample 100 respondents. Based on calculation result that done by means of help prodgram amos ver. 5.0 know training variable, discipline and employee performance produces regression weight (facto loading) statistically significance (sig. < 0.001). this matter shows that each indicator from training variable, discipline and ekmployee performance significant. From analysis result shows each value constuct reliability (cr) > 0.70 that mean that overall training varialbe indicator, discipline and empoyee performance reliabel and from validity test result is known that as a whole factor loadings statistically sig. < 0.05 so that infrential that is factor overall for training variable, discipline and empoyee performance valid.Analysis result uses uji-t show that refression weight from X1 that is γ1 = 0.0119 , 0.05. thereby inferential that found influence significant training variable towards employee performance at Dinas Pendadapatan, Pengelolaan Keuangan dan Aset Daerah (DPPKAD) Pemkot Batu. Analysis result uses uji-t show that regression weight from X2 that is γ1 = 0.00431 < 0.05. tereby inferential that found influence significant discipline variable towards employee performance at Dinas Pendadapatan, Pengelolaan Keuangan dan Aset Daerah (DPPKAD) Pemkot Batu. Key words : Training, Discipline, Performance Employees